Feng Shui dalam Mendesain Logo - Monica Monica (Humaniora, 2011)
A good logo is a reflection of a corporate identity, vision and mission, as well as a summary of the company's character. Feng shui is the ancient Chinese science of topography is believed to affect the success of making a good logo. According to Feng shui, every color, shape, letters, and numbers can affect the energy contained in the company logo. And these factors also have a grouping of the elements of each, a case of elements of earth, metal, fire, wood, and water. If the combination of the elements is wrong, it will create a destructive energy flowing so that hamper the pace of corporate fortunes. With the approach of the study and literature review, this article will explain how the relationship between the selection of colors, shapes, letters, and numbers in accordance with Feng Shui and may still have some artistic value.